2015
DOI: 10.1007/s11336-015-9457-x
|View full text |Cite|
|
Sign up to set email alerts
|

On the Link between Cognitive Diagnostic Models and Knowledge Space Theory

Abstract: The present work explores the connections between cognitive diagnostic models (CDM) and knowledge space theory (KST) and shows that these two quite distinct approaches overlap. It is proved that in fact the Multiple Strategy DINA (Deterministic Input Noisy AND-gate) model and the CBLIM, a competence-based extension of the basic local independence model (BLIM), are equivalent. To demonstrate the benefits that arise from integrating the two theoretical perspectives, it is shown that a fairly complete picture on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 37 publications
0
53
0
1
Order By: Relevance
“…However, in the other six spaces the correspondence between competence states and performance states is many‐to‐one. In C3, for instance, both competence states ∅ and { d } are mapped to the performance state ∅, whereas both competence states { a } and { a , d } are mapped to performance state {1} (the reader interested in the conditions that a skill function must satisfy to have a one‐to‐one correspondence between competence and performance states is referred to Heller, Stefanutti, Anselmi, & Robusto, , ).…”
Section: A Simulation Studymentioning
confidence: 99%
“…However, in the other six spaces the correspondence between competence states and performance states is many‐to‐one. In C3, for instance, both competence states ∅ and { d } are mapped to the performance state ∅, whereas both competence states { a } and { a , d } are mapped to performance state {1} (the reader interested in the conditions that a skill function must satisfy to have a one‐to‐one correspondence between competence and performance states is referred to Heller, Stefanutti, Anselmi, & Robusto, , ).…”
Section: A Simulation Studymentioning
confidence: 99%
“…It is beyond the scope of this paper to examine the use of numbers to describe behaviors in greater detail, but the interested reader may wish to explore the work of Tatsuoka classifying learners using cognitive task analyses employing rule space (Tatsuoka, 2009), the use of partially ordered set theory (Tatsuoka & Ferguson, 2003), and related methods that describe knowledge spaces (e.g., Heller, Stefanutti, Anselmi, & Robusto, 2015).…”
Section: Numbers As Points On a Linementioning
confidence: 99%
“…It was only recently that Robusto (2015, 2016) showed that a particular class of CDMs is equivalent to probabilistic KST models. To be more precise, they proved that the multi-strategy DINA model (MS-DINA; de la Torre & Douglas, 2008) is equivalent to the so-called CBLIM (Heller et al, 2015), a competence-based extension of the basic local independence model (BLIM; Falmagne, 1989;Doignon & Falmagne, 1999), which is the predominant probabilistic model in KST. This includes identifying popular CDMs as submodels of the CBLIM: the DINA model (E. H. Haertel, 1984Haertel, , 1989Haertel, , 1990) is equivalent to the conjunctive CBLIM, and the DINO model (Templin & Henson, 2006) is equivalent to the disjunctive CBLIM.…”
Section: Introductionmentioning
confidence: 99%